The effect of giving verbal feedback during neck stabilisation exercise as an addition to physical therapy in patients with chronic neck pain: A randomised controlled trial. (February 2022) - Lin, Yi-Jia; Hsu, Wei-Chun; Hsieh, Lin-Fen; Chang, Kae-Chwen; Kuo, Ying-Chen; Hsieh, Tien-Lee
Objectives: To study the addition of feedback-guided neck strength home exercise to physical therapy as an enhanced rehabilitation programme in the treatment of patients with chronic neck pain. Design: A prospective randomised controlled trial. Setting: Rehabilitation department of an academic hospital. Subjects: Patients with chronic neck pain. Interventions: The patients in both groups received supervised physical therapy sessions 3 times a week for 12 weeks. Patients in Group A ( N  = 38) used the neck strengthening exerciser device for 20 min daily at home for 6 weeks and patients in Group B ( N  = 20) performed 20 min of daily regular neck exercise at home for 6 weeks. Outcome measures: Neck disability index, pain visual analogue scale, active range of motion of the neck, Patient Global Assessment and patient evaluation of treatment effect. All subjects were assessed at baseline as well as at 6- and 12-week follow-ups. Results: At the 6-week follow-up, Group A exhibited significantly greater improvements ( P  < 0.05) in pain Visual Analogue Scale (Group A: 2.97 ± 1.57; Group B: 4.20 ± 1.82), neck disability index (Group A: 13.95 ± 8.07; Group B: 20.07 ± 9.14) and active cervical extension (Group A: 65.26 ± 12.76; Group B: 51.45 ± 11.78). At 12-week follow-up, Group A also exhibited significantly greater active cervical extension (Group A: 67.74 ± 11.94; Group B: 53.85 ± 14.09; P  < 0.05). Conclusion: Adding neck strengthening exerciser home training to physical therapy was demonstrated to be more effective than physical therapy alone for patients with chronic neck pain.